Synthesis, molecular docking and dynamic studies of 3-cyano-6-hydroxy-5-pentaloxy N-Boc Cyclohexene as key intermediate for oseltamivir phosphate - Zurhana Mat Hussin,; Najmah P.S Hasan,; Fazni Susila Abd Ghani,; Shaari Daud,; Mohd Salleh Rofiee,; Syahrul Imran,; Mohd Tajudin Mohd Ali, (Penerbit Universiti Kebangsaan Malaysia, 2025)
A key intermediate for oseltamivir phosphate synthesis, compound 15 (3-cyano-6-hydroxy-5-pentaloxy-N-Boccyclohexene), was synthesized from inexpensive, commercially available 1,4-cyclohexadiene (4). The synthesis involved eight steps, sequentially introducing substituents onto a cyclohexene ring: An amino group at C1, hydroxy at C6, pentaloxy at C5, and cyano at C3. C1 amination was achieved via epoxidation and asymmetric ring opening using a salen complex and TMSN₃. The C6 hydroxy group was introduced via one-pot reduction and amine protection. C5 functionalization involved allylic oxidation (SeO₂/TBHP) and etherification with 3-pentanol. The C3 cyano group was formed via olefin epoxidation, TMSCN ring opening, and elimination. Molecular docking showed compound 15 had a binding energy of -7.14 kcal/ mol, comparable to oseltamivir (-8.5 kcal/mol), suggesting strong neuraminidase binding. A 200 ns molecular dynamics simulation confirmed complex stability, with RMSF analysis indicating stable interactions. The ADMET profile indicates that these compounds exhibit good drug-like properties, including high gastrointestinal (GI) absorption, good solubility, and no inhibition of CYP450 enzymes.